Achieving a satisfactory clinical and biochemical response in antiphospholipid syndrome and severe thrombocytopenia with rituximab: two case reports. Issue 6 (18th April 2017) - Gamoudi, Donia; Cutajar, Melanie; Gamoudi, Nadia; Camilleri, David James; Gatt, Alex
Key Clinical Message: In AP syndrome (APS) with severe thrombocytopenia, rituximab represents a unique drug which can balance the effect of bleeding and thrombosis. By reducing the production of autoantibodies, rituximab can simultaneously raise the platelets and reduce the chance of thrombosis by suppressing APL antibodies. Rituximab can supersede splenectomy as second‐line therapy in similar patients. Abstract : In AP syndrome (APS) with severe thrombocytopenia, rituximab represents a unique drug which can balance the effect of bleeding and thrombosis. By reducing the production of autoantibodies, rituximab can simultaneously raise the platelets and reduce the chance of thrombosis by suppressing APL antibodies. Rituximab can supersede splenectomy as second‐line therapy in similar patients.